A distinctive new species of the alpheid genus Salmoneus Holthuis, 1955 (Crustacea: Decapoda: Caridea) from the northwestern Pacific - Komai, Tomoyuki; Anker, Arthur (Zootaxa, 2012)
A new species of the alpheid shrimp genus Salmoneus Holthuis, 1955, S. pinguis sp. nov., is described based on the ho-lotype from Okinawa, Ryukyu Archipelago, Japan. An additional, much smaller and morphologically slightly differentspecimen from Panglao, Bohol Sea, the Philippines, is tentatively assigned to S. pinguis. sp. nov. The new species is oneof the most unusual members of Salmoneus presenting a combination of several unique characters, including the unusuallystout, plump body; the carapace strongly domed dorsally, with a broadly rounded rostrum, and without orbital teeth; thesecond abdominal pleuron conspicuously enlarged; the fourth pleuron greatly overlapping the fifth pleuron; the antennularand antennal flagella furnished with long setae; and the major cheliped comparatively small, and with the distally blunt, slightly bulbous fingertips.